Jeeves and the wedding bells - Faulks, Sebastian (St. Martin's Press, 2013)
"Bertie Wooster (a young man about town) and his butler Jeeves (the very model of the modern manservant)--return in their first new novel in nearly forty years: Jeeves and the Wedding Bells by Sebastian Faulks. P.G. Wodehouse documented the lives of the inimitable Jeeves and Wooster for nearly sixty years, from their first appearance in 1915 ("Extricating Young Gussie") to the his final completed novel (Aunts Aren't Gentlemen) in 1974. These two were the finest creations of a novelist widely proclaimed to be the finest comic English writer by critics and fans alike. With the approval of the Wodehouse estate, acclaimed novelist Sebastian Faulks brings Bertie and Jeeves back to life in a hilarious affair of mix-ups and mishaps. Bertie, nursing a bit of heartbreak over the recent engagement of one Georgiana Meadowes to someone not named Wooster, agrees to "help" his old friend Peregrine "Woody" Beeching, whose own romance is foundering. Almost immediately, things go awry and the simple plan quickly becomes complicated. Jeeves ends up having to impersonate one Lord Etringham, while Bertie plays the part of Jeeves' manservant "Wilberforce"--and this all happens under the same roof as the now affianced Ms. Meadowes. From there the plot becomes even more hilarious and convoluted, in a brilliantly conceived, seamlessly written comic work worthy of the master himself"--